2012
DOI: 10.1002/cbf.2917
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy enhances apoptosis induced by the PI3K/AKT/mTor inhibitor NVP‐BEZ235 in renal cell carcinoma cells

Abstract: The PI3K/AKT/mTOR pathway plays a key role in the development of the hypervascular tumor renal cell carcinoma (RCC). NVP-BEZ235 (NVP), a novel dual PI3K/mTOR inhibitor, showed great antitumor benefit and provided a treatment strategy in RCC. In this study, we test the effect of NVP on survival rate, apoptosis and autophagy in the RCC cell line, 786-0. We also explore the hypothesis that NVP, in combination with autophagy inhibitors, leads to apoptosis enhancement in 786-0 cells. The results showed that the PI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 50 publications
(85 reference statements)
0
34
0
Order By: Relevance
“…However in vivo these agents may prove to be less effective than traditional mTOR inhibitors, because they do not display additional effects on the tumor microenvironment compared to those conferred by classical compounds [62]. Yet another emerging approach to overcome resistance is a use of dual inhibitors targeting autophagy [73]. Dual inhibitors of mTOR in combination with autophagy inhibitors has proven to enhance the suppression of growth and induction of apoptosis in ccRCC cell lines.…”
Section: Novel Dimensions In Comprehensive Approach the Mechanisms Ofmentioning
confidence: 99%
“…However in vivo these agents may prove to be less effective than traditional mTOR inhibitors, because they do not display additional effects on the tumor microenvironment compared to those conferred by classical compounds [62]. Yet another emerging approach to overcome resistance is a use of dual inhibitors targeting autophagy [73]. Dual inhibitors of mTOR in combination with autophagy inhibitors has proven to enhance the suppression of growth and induction of apoptosis in ccRCC cell lines.…”
Section: Novel Dimensions In Comprehensive Approach the Mechanisms Ofmentioning
confidence: 99%
“…Consistent with this observation, Manara et al showed that NVP-BEZ235 induced sarcoma stasis, by arresting cells in G1 phase of the cell cycle, without remarkable effects on apoptosis (13). It was postulated that autophagy induced by NVP-BEZ235 was a pro-survival mechanism which rendered tumor cells capable of anti-apoptosis surviving in the kinase inhibitor (25)(26)(27).…”
Section: Discussionmentioning
confidence: 85%
“…However, studies have shown that induction of autophagy can promote either cell survival or death in RCC cells. Inhibition of mTOR pathway induced autophagy in several RCC cell lines (7,49,104,105), but autophagy inhibitor chloroquine promoted cell death by preventing autophagy and inducing RIP kinase-and ROSmediated necroptosis in RCC cell line (RCC4) and suppressed xenograft growth (7), whereas PI3K/mTOR inhibitor suppressed cell growth and induced apoptosis in RCC cells (786-0) and concomitantly activated autophagy that protected against apoptosis (49,104) (Fig. 7C).…”
Section: Implication Of Kidney Autophagy In Genetic Diseases and Cancermentioning
confidence: 99%